Efektivitas Strategi REACT Terhadap Hasil belajar Siswa Pada Materi Larutan Penyangga Di Kelas XI SMA Negeri 2 Langowan - Zurisaday Taidi; Ardi Kapahang; Meiske Naomi Mamuaja (Oxygenius Journal Of Chemistry Education, 2019)
Chemistry is a science that studies materials that are generally abstract in nature so many students find it difficult to understand the concept of chemistry which causes a lack of interaction between real life and chemical knowledge. This study aims to determine the effectiveness of the REACT strategy in improving student learning outcomes in buffering material at SMA Negeri 2 Langowan. The research method used is Quasi Experiment Design with research design is Posttest-only Control Group Design. The population is all students of class XI Science in SMA Negeri 2 Langowan even semester 2017/2018. The sample of this study were all students of class XI IPA 1, amounting to 25 people as the experimental class and all students of class XI IPA 2, amounting to 21 people as the control class. Data collected is processed from the results of Posttest. Data were analyzed using the Independent t-test formula to test the research hypotheses and obtained tcount> ttable (7.99> 2.02), so it can be concluded that the Contextual Teaching and Learning (CTL) learning method with REACT strategy proved to be effective against improving student learning outcomes in buffer material in class XI IPA of SMA Negeri 2 Langowan.